2005
DOI: 10.1111/j.1523-1739.2005.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Regional Patterns of Similarity in Species Composition for Conservation Planning

Abstract: In a review of recent challenges in conservation planning, Ferrier (2002) proposed the incorporation of models of similarity in species composition as a means for prioritizing areas for biodiversity conservation. A key assumption of this approach is that estimates of compositional similarity derived from models of similarity in species composition can be used as effective surrogates for real similarity data. We used data on snail distribution in Israel to test this assumption. We used two types of models to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 67 publications
2
51
0
1
Order By: Relevance
“…Although surrogates have been employed, this process is typically based on information on the spatial distribution (and abundance) of key species (Steinitz et al 2005;Grenyer et al 2006). For most groups and places adequate information is not available, and increasing reliance is being placed on modelling species distributions (Guisan & Thuiller 2005;Moisen et al 2006): an approach that has been criticized on several grounds.…”
Section: Habitat Alteration (A) Habitat Alteration and Changing Climatesmentioning
confidence: 99%
“…Although surrogates have been employed, this process is typically based on information on the spatial distribution (and abundance) of key species (Steinitz et al 2005;Grenyer et al 2006). For most groups and places adequate information is not available, and increasing reliance is being placed on modelling species distributions (Guisan & Thuiller 2005;Moisen et al 2006): an approach that has been criticized on several grounds.…”
Section: Habitat Alteration (A) Habitat Alteration and Changing Climatesmentioning
confidence: 99%
“…Beta diversity has been used to test nichebased models against neutral models of species assembly (e.g., Ruokolainen et al 1997;Condit et al 2002;Tuomisto et al 2003;Chust et al 2006) and for the evaluation of distance decay at continental scales (Nekola and White 1999;Qian et al 1998). To a smaller extent, the concept has also been employed in conservation-related studies (e.g., Steinitz et al 2005;Wiersma and Urban 2005) or in studies on biological homogenization (e.g., McKinney 2004; Jurasinski and Kreyling 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also reported cross-taxon congruence in community similarity (or complementarity) (e.g. Howard et al 1998;Oliver et al 1998;Moritz et al 2001;Steinitz et al 2005;Su et al 2004;Pawar et al 2007). Dispersal capacity has been shown to infl uence the degree of cross-taxon congruence in community similarity (Moritz et al 2001;Graham et al 2006;Pawar et al 2007).…”
Section: Patterns In Assemblage Compositionmentioning
confidence: 99%